O ensino da matemática através da resolução de problemas e do uso da arte no 6º ano do ensino fundamental - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
The objective was to understand how the classroom practices involving problem solving in mathematics classes are developed through art in the 6th grade classes of elementary school, developed at the Municipal School of Early Childhood Education and Elementary School Twenty-July , located in the community of Correio do Tapará, in the municipality of Santarém, in the west of Pará. The research method was based on the bibliographical references for a better understanding of the content and the application of activities in the 6th grade class to verify the students' performance on the use of art in the teaching of mathematics, where 9 students participated, being developed in two stages to differentiate their knowledge. It was found that students before the explanations and without the use of concrete materials, solved using the procedures that each one obtained according to its form. After explaining the problems and making use of the concrete tools, they had another vision and new procedures for their resolutions and improvement in their results, but they felt difficulty with the materials, because they have no customs in the process of teaching mathematics.
Keywords: Matemática; Problemas; Arte; Ensino; Aprendizagem; CNPQ:: CIÊNCIAS EXATAS E DA TERRA